LIVING THE LIVE WITH HEALTHY EXPERIENCES: NEW-AGE ELDERLY IN GERMANY - Loureiro, S. M. C.; J. Middendorf (Proceedings of the International conference on Tourism and Ageing., 2016)
The aims of this study are to analyze which potential attributes of anti-ageing experiences (goods, services, experiences) will tend to be associated to subjective happiness; how cognitive age is associated to mindfulness; and the influence of mindfulness on subjective happiness.